Developing Innovations to Enhance Ethics and Morality in Preventing Corruption Among Police Officers in the Performance of Their Duties - Khundiloknattawasa, suwanna; Nakphuang, Akkalak; Kongmaklom, Kittipat; khundiloknattawasa, Rachata; Piyawatchanaporn, Worathep; Tantiphantharak, Sakarin; Saedan, Natthida (Journal of Thai Ombudsman, 2026)
This research aims to develop innovative approaches to enhance ethics and morality in preventing corruption among police officers. The goal is to raise awareness of anti-corruption among police personnel. A platform was designed and developed to promote ethical conduct, pride in the police profession, and the courage to stand up for what is right in combating corruption. This mixed-method research involved data collection through in-depth interviews, focus group discussions, workshops, and an evaluation of the effectiveness of the application designed to promote ethics, morality, and anti-corruption awareness among police officers. The findings indicate that: (1) The developed COPDee platform is user-friendly and secure, with functions including receiving information about anti-corruption activities and prevention, reporting corruption among police officers, recognizing ethical officers, providing a forum for discussion, and using a chatbot to provide automated information via a messaging application. (2) The overall evaluation of the COPDee platform’s usability was at the highest level (x̄ = 4.62, SD. = 0.57).